A new species of Semisulcospira O. Boettger, 1886 (Gastropoda, Cerithoidea, Semisulcospiridae) from Fujian, China with mitochondrial genome and its phylogenetic implications - Yi-Bin Xu; Yuan-Zheng Meng; Sheng Zeng; Hang-Jun Wang; Shen Zhong; De-Yuan Yang; Xi-Ping Zhou; Christopher J. Glasby (Zoosystematics and Evolution)
During our investigation of the diversity and phylogeny of the family Semisulcospiridae in China, we have found a presumed new species in mountain streams of Xiamen, Fujian Province on both morphology and molecular evidence. This new species, Semisulcospira egretta sp. nov., is characterized by its thin and smooth shell, retaining about 0.5 mm long embryonic shells in its brood pouch, and by distinctive features of its radular morphology. Phylogenetic analyses of partial sequences of the mitochondrial markers 16S ribosomal RNA (16S) and cytochrome c oxidase subunit I (COI) and complete sequences of the nuclear ribosomal internal transcribed spacer (ITS, including internal transcribed spacer 1, 5.8S ribosomal RNA gene, and internal transcribed spacer 2) supported the distinctiveness of S. egretta sp. nov. from other Semisulcospira species. These analyses consistently placed S. egretta sp. nov. in Semisulcospira confirming its monophyly. Phylogenetic analyses based on just COI and 16S exhibited low resolution rendering the phylogenetic position of the new species within the genus uncertain. In contrast, phylogenetic tree analyses of complete mitochondrial genomes, which include 13 protein-coding genes (PCGs), were better resolved. However, the mitogenome dataset included a more restricted sampling of taxa (16), impeding a detailed exploration of the phylogenetic position of the new species. To address this deficit, we provide seven complete mitochondrial genomes for S. egretta sp. nov., obtained using the genome skimming sequencing method. This study contributes important molecular and genomic data, aiding in the understanding of semisulcospirid phylogeny, and highlights the need for further taxonomic sampling and phylogenomic methods to resolve the evolutionary relationships within Semisulcospiridae.